Table of contents and editorial information - R. E. Stevenson (Journal of Applied Communications, 1971)
Editorial front matter and table of contents for vol. 54, no. 4 (Oct.-Dec 1971) of ACE, the official journal of the American Association of Agricultural College Editors. This issue features major papers and summaries of discussion sessions at the 55th Annual Meeting of AAACE, with an introductory note by Mark Allen, program committee member.